2008
DOI: 10.1016/j.jnn.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory distress syndrome degrades the fine structure of the non-nutritive suck in preterm infants

Abstract: AIMS AND OBJECTIVES: Suck development is a challenging hurdle for preterm infants who endure an extensive oxygen history due to respiratory distress syndrome (RDS). The fine structure of the non-nutritive suck (NNS) was studied in preterm infants according to RDS severity. DESIGN AND METHODS: Recordings of NNS were completed cribside in the neonatal intensive care unit (NICU) in 55 preterm infants distributed among one healthy control group and two RDS infant groups. NNS pressure amplitude (cmH(2)0) and within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…[1][2][3] Many of these premature infants have endured an extensive course of respiratory support (oxygen therapy, positive pressure ventilation and/or nasal cannulation) due to the immaturity of the lungs and respiratory disease. As pulmonary function improves, these infants often manifest oromotor dyscoordination, absent or weak non-nutritive suck (NNS), 4,5 poor airway protection, dysphagia 6 and poor state control. 7 Some investigators contend that the invasiveness of lengthy intubation and oxygen supplementation procedures associated with prematurity cost the baby precious sensory and motor experiences during a critical period of brain development for oromotor pattern generation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many of these premature infants have endured an extensive course of respiratory support (oxygen therapy, positive pressure ventilation and/or nasal cannulation) due to the immaturity of the lungs and respiratory disease. As pulmonary function improves, these infants often manifest oromotor dyscoordination, absent or weak non-nutritive suck (NNS), 4,5 poor airway protection, dysphagia 6 and poor state control. 7 Some investigators contend that the invasiveness of lengthy intubation and oxygen supplementation procedures associated with prematurity cost the baby precious sensory and motor experiences during a critical period of brain development for oromotor pattern generation.…”
Section: Introductionmentioning
confidence: 99%
“…Established quantitative measures of NNS dynamics were calculated for each suck sample using an automated waveform discrimination/feature detection algorithm that is implemented on the NTrainer System [2325, 30, 31, 46]. From each 2-minute NNS sampling epoch, nipple compressions exceeding 1 cm H 2 O are automatically selected for waveform discrimination of the infant's non-nutritive suck performance.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, many have concluded that altering the sCPG will also alter the NNS. NNS is characterized by a burst-pause pattern, with 6–12 suck cycles at a frequency of approximately 2 Hz, separated by pause “rest” periods to accommodate respiration [14, 21, 29–31]. Because coordinated NNS is necessary to produce the more difficult suck-swallow-breathe pattern associated with nutritive suck [3235], enhancing the NNS is a logical therapeutic goal for infants with underdeveloped oromotor skills or feeding difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…respiratory disease, can impose limits on the opportunities for sucking. This can deprive the infant of necessary oral sensori-motor experiences during a critical period of brain development when central patterning of suck and feeding skills are being refined (da Costa et al, 2010b;Mizuno et al, 2007;Stumm et al, 2008). Other medical interventions used in preterm infants (e.g.…”
Section: Factors Influencing the Development Of Oral Feeding In The Pmentioning
confidence: 99%